Preparation method of iron-based catalyst, iron-based catalyst and application of iron-based catalyst

The preparation of iron-based catalysts through the combination of Fe salt and additives and microwave hydrothermal treatment solves the problems of high catalyst cost and chromium pollution, and achieves a high-efficiency and low-cost water vapor transformation reaction, with high stability and low methane selectivity.

CN119175099AActive Publication Date: 2024-12-24CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310735536.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24
Estimated Expiration
2043-06-21

AI Technical Summary

Technical Problem

In the existing water vapor transformation reaction, the catalyst costs are high, the chromium pollution is severe and the stability is poor, making it difficult to develop efficient and low-cost chromium-free catalysts.

Method used

The iron-based catalyst is prepared by mixing grinding, hydrothermal treatment and surface modification using Fe salt and additives A, B, and C to form a high-stability and low-cost catalyst. The additive A is selected from Mn, Mo, Co, and Al. , Ce, etc., additive B is selected from Cu, Ni, Pt, etc., additive C is an alkali metal, and is prepared by microwave-assisted hydrothermal treatment and calcination.

Benefits of technology

High hydrogen yield and low methane selectivity under low cost and low water-gas ratio conditions are achieved, and the catalyst maintains good activity at high temperatures, reducing chromium pollution and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004295913530000131
    Figure BDA0004295913530000131
  • Figure BDA0004295913530000132
    Figure BDA0004295913530000132
Patent Text Reader

Abstract

The invention relates to a preparation method of an iron-based catalyst, the iron-based catalyst and application of the iron-based catalyst, and the catalyst is prepared by the following steps: mixing and grinding Fe salt and assistant A salt, then adding a solution of assistant B salt, carrying out hydrothermal treatment, washing and drying to obtain a precursor; and loading the auxiliary C on the precursor, drying and roasting to obtain the iron-based catalyst. The catalyst is applied to water-gas shift reaction, is suitable for the condition of low water-gas ratio, can improve the hydrogen yield of water-gas shift and reduce the methane selectivity, has good heat-resistant activity, and keeps good specific surface and activity after high-temperature treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an iron-based catalyst for a water-gas shift reaction, in particular to a method for preparing the iron-based catalyst, the obtained iron-based catalyst and application thereof. Background Art

[0002] In the context of carbon neutrality, hydrogen energy has attracted much attention as a potential substitute for traditional fossil fuels. In the past decade, the hydrogen energy economy has developed rapidly. The total calorific value of hydrogen fuel is 141.8MJ / kg, which is twice as high as the total calorific value of natural gas (54.0MJ / kg), and has good economic performance. Although hydrogen resources are abundant, such as water and biomass, most of the hydrogen today is extracted from traditional fossil fuels, such as crude oil and natural gas. At present, methane steam reforming (SRM) is the main mature industrial hydrogen production technology. In order to increase the hydrogen yield, the reforming process needs to be followed by a water-gas shift reaction to react the excess CO and further increase the H2 content in the atmosphere, thereby increasing the hydrogen yield. In recent years, another important application of the water-gas shift reaction is in the field of new energy vehicles. The electrode material of the fuel cell is mainly composed of Pt, which is easily deactivated in the presence of carbon monoxide. Therefore, the water-gas shift reactor is placed before the fuel cell to convert carbon monoxide into hydrogen and CO2 gas. It can be seen that the water-gas shift reaction (WGS) plays an important industrial role in regulating and increasing the H2 concentration.

[0003] Commercial iron oxide catalysts with chromium oxide as a structural promoter have been used for more than 60 years. Cr2O3 / CrO3, in addition to acting as a structural promoter to prevent the sintering of iron oxide crystals, can also enhance the intrinsic catalytic activity of Fe2O3. Under high temperature hydrothermal conditions during the reaction, Cr2O3 inhibits the growth of iron oxide crystals and avoids a significant reduction in the specific surface area of ​​the catalyst. Although chromium oxides have been proven to be good promoters, hexavalent chromium is a heavy metal that is toxic to humans, organisms or cells and is also a serious environmental pollutant. The water solubility of hexavalent chromium causes it to leach from the catalyst through condensed steam or cold water. The hexavalent chromium (Cr6+) of fresh and discarded commercial high temperature shift Fe-Cr catalysts is very expensive to handle. Due to the toxicity and environmental impact of hexavalent chromium (Cr6+), a highly stable and active chromium-free catalyst is needed for HT-WGSR.

[0004] CN107649142B discloses a low-density iron-chromium CO conversion catalyst, which uses Mn, Mg, and Cr as additives to improve the high-temperature stability of the Fe-based catalyst. The catalyst is Fe2O3, Cr2O3, CuO, Mn, Mg, and Cr. x O YThe main components of the mixture are as follows by weight percentage: Fe2O3 70% to 92%, Cr2O3 4% to 15%, CuO 0.5% to 10%, M x O Y 4% to 15%, wherein M is one or more of Ti, Mg, Mn, Al, Ca, and Si.

[0005] CN103272600B discloses a supported copper-iron water-gas shift catalyst, which uses modified bauxite as a carrier, Cu and Fe as active components, and the copper oxide content is 10-15wt% and the iron oxide content is 5-30wt% in terms of oxide mass percentage; the supported copper-iron water-gas shift catalyst is prepared by a parallel flow co-precipitation method.

[0006] CN104014345B discloses a CuO-CeO2 catalyst for water-gas shift reaction. The obtained CuO-CeO2 catalyst consists of an active component CuO and a CeO2 carrier, wherein the CuO content is 5 to 30 wt%. The catalyst is prepared by a complex deposition precipitation method.

[0007] The problems of water gas shift reaction reported in literature and patents include serious methanogenic side reactions, low time-space yield, high catalyst cost, serious chromium pollution, etc. Therefore, how to develop chromium-free, highly selective, and simple preparation process catalysts under the premise of ensuring hydrothermal stability is the difficulty and direction of realizing the industrial application of green shift catalysts. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing an iron-based catalyst, the obtained iron-based catalyst and its application on the basis of the prior art, so as to solve the problem of high cost in the preparation process of the iron-based catalyst in the prior art.

[0009] The first aspect of the present invention provides a method for preparing an iron-based catalyst, comprising the following steps:

[0010] (1) mixing and grinding Fe salt and auxiliary agent A salt to obtain a mixed material I;

[0011] The additive A is selected from one or more of Mn, Mo, Co, Al, Ce, La, V, Ni, Mg, and Ca, and the element molar ratio of Fe to the additive A is 2:1-30:1;

[0012] (2) mixing the precipitant with the mixed material I obtained in step (1), and continuing to grind for a certain period of time to obtain a mixed material II;

[0013] (3) providing a solution containing a salt of an auxiliary agent B, and adding the solution to the mixed material II obtained in step (2), and continuing to grind and mix for a certain period of time to obtain a mixed material III;

[0014] The additive B is selected from one or more of Cu, Ni, Pt, and Pd, and the element molar ratio of Fe to the additive B is 10:1-200:1;

[0015] (4) sending the mixed material III obtained in step (3) to a hydrothermal kettle for hydrothermal treatment, and then washing and drying to obtain a precursor;

[0016] (5) Loading the above-mentioned precursor with an auxiliary agent C, drying it, and calcining it to obtain an iron-based catalyst, wherein the auxiliary agent C is selected from at least one of the alkali metals Na, K, and Cs.

[0017] In one embodiment of the present invention, a ball mill is used for grinding in step (1), and the grinding time is 2 min to 60 min;

[0018] In step (2), a ball mill is used for grinding, and the grinding time is 2 min to 60 min;

[0019] In step (3), a ball mill is used for grinding, and the grinding time is 2 min to 60 min.

[0020] In one embodiment of the present invention, the additive A is selected from one or more of Mn, Al, Ni, and Ce;

[0021] The Fe salt and the additive A salt are independently selected from at least one of Fe and additive A's nitrate, sulfate, formates, acetates and halides.

[0022] In one embodiment of the present invention, in step (2), the precipitating agent is one or more selected from ammonium carbonate, urea, sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, and ammonium hydroxide;

[0023] The molar dosage of the precipitant is 1-5 times the theoretical stoichiometric ratio of the total number of metal atoms of Fe, auxiliary agent A and auxiliary agent B.

[0024] In one embodiment of the present invention, in step (3), the additive B salt is dissolved in deionized water to obtain a solution containing the additive B salt, wherein the additive B salt is selected from at least one of the nitrate, sulfate, formate, acetate, and halide of the additive B;

[0025] In the solution containing the additive B salt, the concentration of the additive B element is 10-100 mol / L, preferably 20-50 mol / L;

[0026] Calculated as elements, the molar ratio of Fe to additive B is 10:1 to 100:1.

[0027] In a preferred case, the additive B is selected from at least one of Cu and Ni.

[0028] In one embodiment of the present invention, in step (4), the reaction temperature of the hydrothermal treatment is 80-250° C., and the reaction time is 1-72 h.

[0029] In a preferred embodiment of the present invention, in step (4), the hydrothermal treatment is microwave-assisted hydrothermal treatment, and the conditions of the microwave-assisted hydrothermal treatment are: reaction temperature 100-250°C, microwave output power 500-1500W, and reaction time 1-8h.

[0030] In one embodiment of the present invention, in step (4), the drying temperature is 60-150° C., the drying time is 0.5-8 h,

[0031] Preferably, the drying temperature is 80-120° C. and the drying time is 1-4 h.

[0032] In one embodiment of the present invention, the amount of the additive C added in step (5) is such that, calculated as oxide, the mass fraction of the additive C to the iron-based catalyst is 0.1-10%.

[0033] In one embodiment of the present invention, the method for loading the auxiliary agent C onto the precursor is: mechanically mixing at least one of the oxide, inorganic salt, and organic metal compound of the auxiliary agent C with the precursor.

[0034] In another embodiment of the present invention, the method for loading the auxiliary agent C onto the precursor is: impregnating the precursor with a solution containing at least one of an inorganic salt and an organic metal compound of the auxiliary agent C.

[0035] In one embodiment of the present invention, in step (5), the drying temperature is 60-150°C, the drying time is 0.5h-8h, the roasting temperature is 200-600°C, and the roasting time is 1-10h;

[0036] Preferably, the drying temperature is 80-120°C and the drying time is 1-4h.

[0037] Preferably, the calcination temperature is 300-550° C. and the calcination time is 1-8 h.

[0038] In one embodiment of the present invention, when the precursor is impregnated with a solution of at least one of an inorganic salt and an organic metal compound containing an auxiliary agent C, rotary evaporation is preferably performed before drying, and the rotary evaporation temperature is 30-80°C, the vacuum degree is 0.1MPa, and the rotary evaporation time is 0.2-2h.

[0039] The preparation method of the present invention is used to form a solid solution between the additive A and the Fe-based catalyst, thereby promoting the Fe 2+ with Fe 3+In addition, the additive A plays a role in physically isolating the active phase, preventing the catalyst from sintering and improving stability. Furthermore, in the present invention, the additive C is used for surface modification to adjust the surface acidity and alkalinity of the iron-based catalyst and promote the water vapor shift reaction.

[0040] The second aspect of the present invention provides an iron-based catalyst obtained by the above-mentioned preparation method, based on the iron-based catalyst as a whole, calculated as oxide, the Fe content is 70-95%, the additive A content is 1-20%, the additive B content is 0.1-10%, and the additive C content is 0.1-10%; the additive A is selected from one or more of Mn, Mo, Co, Al, Ce, La, V, Ni, Mg, and Ca, the additive B is selected from one or more of Cu, Ni, Pt, and Pd, and the additive C is selected from at least one of alkali metals Na, K, and Cs.

[0041] The third aspect of the present invention provides an application method of the iron-based catalyst obtained by the above preparation method, wherein the iron-based catalyst is loaded in a fixed bed reactor for a water gas shift reaction, and the reaction conditions are: pressure 0.1-5MPa, temperature 300-500°C, volume space velocity 2000-100000h -1 , nH2O:nCO in the raw gas = 2.4-4.

[0042] In one embodiment of the present invention, the iron-based catalyst is subjected to reduction pretreatment before use, the pretreatment atmosphere is H2 / CO / H2O or H2 / CO / H2O / CO2, the pretreatment temperature is 200-600°C, the pretreatment time is 1-12h, the pretreatment pressure is 0.1-1MPa, and the pretreatment volume space velocity is 500-20000h -1 .

[0043] Features of the present invention:

[0044] (1) The present invention utilizes a mechanical solid phase reaction with little solvent, i.e., adopts a simple and efficient preparation method with little solvent. On the one hand, it omits the neutralization and aging steps of the iron-based catalyst precipitation in the prior art, thus shortening the preparation time. On the other hand, it reduces the solvent cost in the preparation process and reduces the wastewater treatment cost.

[0045] (2) The hydrothermal treatment process of the present invention has a fast nucleation speed, uniform dispersion, high nucleation rate, low energy consumption and short time consumption.

[0046] (3) The present invention adopts surface modification and regulation to obtain an active phase with medium-strong alkalinity for suitable adsorption, which exhibits excellent performance of high activity and high stability in the field of water vapor conversion.

[0047] (3) The Fe-based catalyst of the present invention is low in cost and is suitable for conditions with low water-gas ratios. It can increase the hydrogen yield of water-gas shift and reduce methane selectivity. At the same time, the catalyst has good heat resistance and activity, and the specific surface area and activity are maintained well after high-temperature treatment. DETAILED DESCRIPTION

[0048] The following examples will further illustrate the present invention. However, the present invention is not limited thereto.

[0049] The catalysts in the examples and comparative examples were tested for BET specific surface area and pore volume:

[0050] The specific surface area and pore volume of the catalyst were analyzed by low-temperature N2 constant temperature adsorption-desorption and conventional BET calculation. Before analysis, the sample was dried at 120℃ for 2h and then evacuated under vacuum at 300℃. The adsorption medium was high-purity nitrogen. The adsorption / desorption experiment was carried out under liquid nitrogen cooling conditions (-196℃).

[0051] Example 1

[0052] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0053] (1) 20 g of ferric nitrate nonahydrate and 1.86 g of aluminum nitrate nonahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0054] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0055] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 15 min.

[0056] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0057] (5) 0.11 g of cesium carbonate was dissolved in 20 mL of deionized water to obtain a cesium carbonate solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 55° C. and a vacuum degree of 0.1 MPa for 1 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-1. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0058] Example 2

[0059] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0060] (1) 20 g of ferric nitrate nonahydrate and 1.42 g of manganese nitrate hexahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0061] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0062] (3) Dissolve 0.7 g of nickel nitrate hexahydrate in 5 g of deionized water, add the solution to the powder obtained in step (2), and continue grinding for 5 min.

[0063] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0064] (5) 0.12 g of potassium hydroxide was dissolved in 20 mL of deionized water to obtain a potassium hydroxide solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 50° C. and a vacuum degree of 0.1 MPa for 1 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-2. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0065] Example 3

[0066] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0067] (1) 20 g of ferric nitrate nonahydrate and 1.44 g of nickel nitrate hexahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0068] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0069] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 5 min.

[0070] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0071] (5) 0.14 g potassium carbonate was dissolved in 20 mL deionized water to obtain a potassium carbonate solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 55° C. and a vacuum degree of 0.1 MPa for 4 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-3. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0072] Example 4

[0073] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0074] (1) 20 g of ferric nitrate nonahydrate and 0.72 g of nickel nitrate hexahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0075] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0076] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 15 min.

[0077] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0078] (5) 0.11 g of cesium carbonate was dissolved in 20 mL of deionized water to obtain a cesium carbonate solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 45° C. and a vacuum degree of 0.1 MPa for 1 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-4. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0079] Example 5

[0080] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0081] (1) 20 g of ferric nitrate nonahydrate and 0.72 g of nickel nitrate hexahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0082] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0083] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 5 min.

[0084] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0085] (5) 0.14 g potassium carbonate was dissolved in 20 mL deionized water to obtain a potassium carbonate solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 55° C. and a vacuum degree of 0.1 MPa for 1 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-5. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0086] Example 6

[0087] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0088] (1) 20 g of ferric nitrate nonahydrate, 1.1 g of cerium nitrate hexahydrate, and 0.72 g of nickel nitrate hexahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0089] (2) Add 15 g of NaOH and 15 g of Na2CO3 to the powder obtained in step (1) and continue grinding for 15 min.

[0090] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 5 min.

[0091] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180°C at a frequency of 2.45 GHz, kept at this temperature for 8 hours, then the microwave heating was stopped, the temperature was naturally lowered and aged for 2 hours, washed with deionized water 10 times, 500 ml each time, and dried at 120°C for 4 hours to obtain a precursor.

[0092] (5) 0.14 g potassium carbonate was dissolved in 20 mL deionized water to obtain a potassium carbonate solution, and the precursor obtained in step (4) was impregnated with the solution. After impregnation, the sample was first dried by rotary evaporation at a temperature of 50° C. and a vacuum degree of 0.1 MPa for 1 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-6. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0093] Example 7

[0094] The preparation process of the iron-based catalyst of this embodiment is as follows:

[0095] (1) 20 g of ferric nitrate nonahydrate and 1.86 g of aluminum nitrate nonahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0096] (2) Add 20 g of ammonium hydroxide to the powder obtained in step (1) and continue grinding for 15 min.

[0097] (3) Dissolve 0.40 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 15 min.

[0098] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0099] (5) 0.103 g of cesium carbonate was mixed with the precursor obtained in step (4), and then ground in a ball mill for 20 min. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst C-7. BET specific surface area and pore volume test were performed, and the results are shown in Table 1.

[0100] Comparative Example 1

[0101] This comparative example adopts precipitation method to obtain iron-based catalyst:

[0102] 20g of ferric nitrate nonahydrate, 1.44g of nickel nitrate hexahydrate, and 0.60g of copper nitrate trihydrate were dissolved in 150mL of deionized water to obtain solution A. 40g of ammonia water (mass fraction 25% to 28%) was dissolved in 70mL of deionized water to obtain solution B. Solution B was added to solution A at 5mL / min through a peristaltic pump, stirred at room temperature for aging for 2h, washed three times with deionized water, filtered three times, and dried at 120°C for 4h to obtain a precursor.

[0103] 0.14 g potassium carbonate was dissolved in 20 mL aqueous solution to obtain a potassium carbonate solution, and the precursor obtained above was impregnated with the solution. After impregnation, it was first dried by rotary evaporation at a temperature of 120° C. and a vacuum degree of 0.1 MPa for 4 h. The obtained sample was dried at 120° C. for 2 h, and then calcined at 500° C. for 2 h to obtain catalyst D-1. BET specific surface and pore volume tests were performed, and the results are shown in Table 1.

[0104] Comparative Example 2

[0105] (1) 20 g of ferric nitrate nonahydrate and 1.86 g of aluminum nitrate nonahydrate were mixed in a mortar and ground in a ball mill for 10 min into powder.

[0106] (2) Add 15 g KOH and 15 g K2CO3 to the powder obtained in step (1) and continue grinding for 15 min.

[0107] (3) Dissolve 0.60 g of copper nitrate trihydrate in 5 g of deionized water and add it to the powder obtained in step (2), and continue grinding for 15 min.

[0108] (4) The mixture obtained in step (3) was transferred to a hydrothermal reactor, placed in a microwave synthesizer, heated to 180° C. at a frequency of 2.45 GHz, kept constant for 8 hours, then the microwave heating was stopped, the temperature was naturally cooled and aged for 2 hours, washed three times with deionized water, and dried at 120° C. for 4 hours to obtain a precursor.

[0109] (5) The precursor powder was calcined at 500°C for 2 h to obtain catalyst D-2. BET specific surface area and pore volume tests were performed, and the results are shown in Table 1.

[0110] Examples 8-14, Comparative Examples 3-4

[0111] The following examples and comparative examples are applications of the catalysts obtained in Examples 1-7 and Comparative Examples 1-2.

[0112] The catalyst prepared above was tableted at 15 MPa, crushed, and screened for 40-60 mesh catalysts. 0.5 g of the screened catalyst was loaded into a reaction tube with an inner diameter of 8 mm to carry out a water gas shift reaction.

[0113] Restore preprocessing:

[0114] All catalysts were subjected to reduction pretreatment: the pretreatment atmosphere was CO / CO2 / H2 / N2 (volume fraction) = 24.7% / 8.3% / 49.5% / 17.5%, where N2 was the internal standard gas and did not participate in the reaction; the pretreatment temperature was 400°C, the pretreatment time was 2h, the pressure was atmospheric pressure, and the pretreatment dry gas volume space velocity was 16000h -1 , H2O / CO (molar ratio) = 1.6.

[0115] During the formal water vapor shift reaction, the raw gas used is composed of dry gas and water, wherein the composition of the dry gas by volume fraction is as follows: CO / CO2 / H2 / N2=24.7% / 8.3% / 49.5% / 17.5%, wherein N2 is the internal standard gas and does not participate in the reaction; the H2O / CO (molar ratio) in the raw gas is 2.4.

[0116] The reaction conditions used were: 0.5 MPa, dry gas volume space velocity 16000 h -1 , the reaction was carried out at 400°C.

[0117] After the formal reaction was completed, a heat resistance activity test was conducted. The conditions for the heat resistance activity test were as follows: the reaction pressure, feed gas, and space velocity were consistent with the conditions of the formal reaction, the reaction temperature was raised to 530°C and maintained for 2 hours, and then dropped to 400°C and balanced for 1 hour, and then samples were taken and the carbon monoxide conversion rate was calculated after analysis as the heat resistance activity data.

[0118] The liquid product was collected in an ice-water bath and the product composition was analyzed by gas chromatography. The specific evaluation results are shown in Table 2.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an iron-based catalyst, comprising the following steps: (1) mixing and grinding Fe salt and auxiliary agent A salt to obtain a mixed material I; The additive A is selected from one or more of Mn, Mo, Co, Al, Ce, La, V, Ni, Mg, and Ca, and the element molar ratio of Fe to the additive A is 2:1-30:1; (2) mixing the precipitant with the mixed material I obtained in step (1), and continuing to grind for a certain period of time to obtain a mixed material II; (3) providing a solution containing a salt of an auxiliary agent B, and adding the solution to the mixed material II obtained in step (2), and continuing to grind and mix for a certain period of time to obtain a mixed material III; The additive B is selected from one or more of Cu, Ni, Pt, and Pd, and the element molar ratio of Fe to the additive B is 10:1-200:1; (4) sending the mixed material III obtained in step (3) to a hydrothermal kettle for hydrothermal treatment, and then washing and drying to obtain a precursor; (5) Loading the above-mentioned precursor with an auxiliary agent C, drying it, and calcining it to obtain an iron-based catalyst, wherein the auxiliary agent C is selected from at least one of the alkali metals Na, K, and Cs.

2. The preparation method according to claim 1, characterized in that: In step (1), a ball mill is used for grinding, and the grinding time is 2 min to 60 min; In step (2), a ball mill is used for grinding, and the grinding time is 2 min to 60 min; In step (3), a ball mill is used for grinding, and the grinding time is 2 min to 60 min.

3. The preparation method according to claim 1, characterized in that: The additive A is selected from one or more of Mn, Al, Ni and Ce; The Fe salt and the additive A salt are independently selected from at least one of Fe and additive A's nitrate, sulfate, formates, acetates and halides.

4. The preparation method according to claim 1, characterized in that: In step (2), the precipitating agent is one or more selected from ammonium carbonate, urea, sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, and ammonium hydroxide; The molar dosage of the precipitant is 1-5 times the theoretical stoichiometric ratio of the total number of metal atoms of Fe, auxiliary agent A and auxiliary agent B.

5. The preparation method according to claim 1, characterized in that: In step (3), the additive B salt is dissolved in deionized water to obtain a solution containing the additive B salt, wherein the additive B salt is selected from at least one of the nitrate, sulfate, formate, acetate, and halide of the additive B; In the solution containing the additive B salt, the concentration of the additive B element is 10-100 mol / L, preferably 20-50 mol / L; Calculated by element, the molar ratio of Fe to additive B is 10:1-100:1; The additive B is selected from at least one of Cu and Ni.

6. The preparation method according to claim 1, characterized in that: In step (4), the reaction temperature of the hydrothermal treatment is 80-250° C., and the reaction time is 1-72 h.

7. The preparation method according to claim 1, characterized in that: In step (4), the hydrothermal treatment is microwave-assisted hydrothermal treatment, and the conditions of the microwave-assisted hydrothermal treatment are: reaction temperature 100-250° C., microwave output power 500-1500 W, and reaction time 1-8 h.

8. The preparation method according to claim 1, characterized in that: In step (4), the drying temperature is 60-150°C and the drying time is 0.5-8h. Preferably, the drying temperature is 80-120° C. and the drying time is 1-4 h.

9. The preparation method according to claim 1, characterized in that: The amount of the additive C added in step (5) is, calculated as oxide, 0.1-10% by mass of the additive C to the iron-based catalyst; The method of loading the additive C onto the precursor is: mechanically mixing at least one of the oxide, inorganic salt, and organic metal compound of the additive C with the precursor; or, impregnating the precursor with a solution containing at least one of the inorganic salt and organic metal compound of the additive C.

10. The preparation method according to claim 1, characterized in that: In step (5), the drying temperature is 60-150°C, the drying time is 0.5h-8h, the roasting temperature is 200-600°C, and the roasting time is 1-10h; Preferably, the drying temperature is 80-120°C and the drying time is 1-4h. Preferably, the calcination temperature is 300-550°C and the calcination time is 1-8h; When the precursor is impregnated with a solution containing at least one of an inorganic salt and an organic metal compound of the auxiliary agent C, it is preferably subjected to rotary evaporation before drying. The rotary evaporation temperature is 30-80° C., the vacuum degree is 0.1 MPa, and the rotary evaporation time is 0.2-2 h.

11. An iron-based catalyst obtained by any preparation method according to any one of claims 1 to 10, characterized in that: Based on the whole iron-based catalyst, the Fe content is 70-95% in terms of oxide, the additive A content is 1-20%, the additive B content is 0.1-10%, and the additive C content is 0.1-10%. The additive A is selected from one or more of Mn, Mo, Co, Al, Ce, La, V, Ni, Mg, and Ca, the additive B is selected from one or more of Cu, Ni, Pt, and Pd, and the additive C is selected from at least one of alkali metals Na, K, and Cs.

12. A method for using the iron-based catalyst obtained by any preparation method according to any one of claims 1 to 10, characterized in that: The iron-based catalyst is loaded in a fixed bed reactor for water gas shift reaction, and the reaction conditions are: pressure 0.1-5MPa, temperature 300-500°C, preferably 350-400°C, volume space velocity 2000-100000h -1 , nH2O:nCO in the raw gas = 2.4-4.

13. The application method according to claim 12, characterized in that: The iron-based catalyst is subjected to reduction pretreatment before use, the pretreatment atmosphere is H2 / CO / H2O or H2 / CO / H2O / CO2, the pretreatment temperature is 200-600°C, the pretreatment time is 1-12h, the pretreatment pressure is 0.1-1MPa, and the pretreatment volume space velocity is 500-20000h -1 .

Citation Information

Patent Citations

  • A supported copper-iron water-gas shift catalyst and its preparation method

    CN103272600B

  • CuO-CeO2 catalyst for water-gas shift reaction and its preparation method

    CN104014345B

  • A low-density iron-chromium CO conversion catalyst

    CN107649142B

  • Iron-based water gas transformation catalyst and preparation method thereof

    CN102350355A

  • High-temperature sintering type catalyst for preparing light olefins from synthetic gas and preparation method thereof

    CN104275189A

Cited By

  • Preparation method and application of iron-based catalyst constructed by multi-aid confinement

    CN121490772A